Enthalpy Calculation for Pressurized Oxy- coal Combustion - Jingli Huang; Weihong Wu (Institute of Advanced Engineering and Science, 2012)
Oxy-fuel combustion is recognizing one of the most promising available technologies that zero emission accomplishment may be in the offing. With coal burned under the pressure of 6MPa and oxygen-enriched conditions, the high temperature and high pressure gaseous combustion product is composed of 95% CO2 and water-vapor, with the rest of O2, N2 and so on. However, once lauded as classic approach of resolving fuel gas enthalpy calculation pertaining to ideal gas at atmospheric pressure was restrained by pressure limitations. In this paper, the flue gas was assumed by an ideal mixture of four real gases system, and the equations for calculating the flue gas enthalpy were derived by using the cofunction method incorporating with the Dalton’s law of pressure summation based on the Virial equation. Consequently, the results showed that the calculation method on the basis of the Dalton’s law of pressure summation appears to be a reasonable enthalpy values for the 6MPa oxygen-enriched coal combustion as opposed to the inferior cofunction method. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.850